THE INFLUENCE OF CYCLIC MOVEMENT INTENSITY ON THE RATIO OF THE DURATION OF PHASES OF MOTOR ACTIVITY (Physical Culture and Sport: Scientific Perspective, 2025)
The article discusses issues related to the study of phases of motor activity in cyclic sports. A number of examples of determining individual phases are given, in particular in walking, running, kayaking and canoeing, and swimming. Determining the duration of phases and their correlation, changing the duration of phases depending on the mode of operation (intensity, pace of motor actions) is of great importance in the process of better mastering motor actions, improving the technique of performing physical exercises, and increasing the level of competitive activity. Literature analysis allows us to state the lack of scientific works on determining the duration of individual phases and determining the ratio of phases in cyclic sports.An empirical study attempted to determine the duration of the support and non-support phases in rope jumping. The study of the duration of the phases was carried out using video recordings of rope jumping and a storyboard of motor actions. Empirical research was carried out by higher education students of the Faculty of Health, Psychology, Physical Education and Sports during practical classes in the academic discipline of biomechanics. In particular, students were able to gain knowledge and acquire practical skills in determining the time indicators of motor activity performance.The main task of our study was to determine the ratio of the support and non-support phases. As empirical studies and analysis of the obtained materials have shown, the duration of the support and non-support phases at a slow jumping pace (104.16 repetitions per minute) is approximately the same (has a ratio of 49.64% and 50.36%). Increasing the intensity of jumping rope to a rate of 130.59 repetitions per minute leads to a change in the ratio towards an increase in the unsupported phase (53.6% and 46.4%). However, such changes in the ratio of phase duration at different intensities are not significant, as evidenced by the absence of correlations between the rate of motor actions and the ratio between the phases (supported and unsupported). The ratio of phase durations may also depend on the individual characteristics of the performance of the motor action, in particular: the height of the foot lifting from the floor, the amplitude of movements in the knee joints.
Keywords: cyclic sports; motor action phase; support and non-support phases; phase duration